Efectos conductuales y fisiológicos, privación senso-perceptiva prolongada - Zubek, John P. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
After describing some of the historical influences which led to the worldwide experimental interest in sensory' deprivation and the various techniques that have been devised to achieve sensory restriction, a critical review is presented of the main findings. Because of the voluminous nature of the literature which has developed on this topic since 19 5 1, the emphasis in this article is largely placed upon well-controlled laboratory experiments in which human subjects have been exposed to prolonged periods of isolation and confinement.